The Implications of Patriarchal Culture toward Gender Discrimination in Anne with an E Movie Series - Rahma, Haifa (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2023)
ABSTRAK This study aims to identify how patriarchal culture influences to the emergence of gender discrimination behavior and to find out the forms of implementation of female characters in their efforts to resist gender discrimination to achieve equality between men and women in the movie series Anne with an E. Two types of data were used in this research, primary and secondary data. The primary data source is a serial movie entitled Anne with an E. While secondary data sources are supporting references taken from books, journals, and the internet related to the research. The author used a qualitative analysis method and applied Naomi Wolf's theory of liberal feminism to analyze the data. The results of the study concluded that the involvement of patriarchal culture applied in Avonlea society influences the emergence of discriminatory behavior toward female characters in various aspects such as education, employment, marriage and individual autonomy. Moreover, the female characters implemented the feminist movement as a further response to the gender discrimination they experienced by raising awareness through ideology, forming women's empowerment communities, campaigning for freedom of speech and improvisation, evaluating and innovating education, and empowering women to participate in politics. Keywords: Anne with an E, Liberal Feminism, Gender Discrimination, Patriarchy.